The Family Communication Culture Based on Religious Values in Preventing the Drug Use among Muslim Families in Pulo Padang Village - Abdillah Hamdani Ritonga; Muhammad Husni Ritonga (Universitas Negeri Medan, 2022)
The family is the place for the most basic moral education received by children,therefore the family has a significant role in guiding the children for not consumingany drugs. Communication based on religious values created by a family is certainlyvery influential on children in avoiding drug use. This study aimed to determine theculture of family communication based on religious values in preventing drug useamong Muslim families. The method in this research was descriptive qualitativemethod. The results showed that the parties who have a very important role inpreventing drug abuse are families, especially parents. Parents and dearest familyare the closest environment that can influence adolescent’s behavior. Therefore, therole of parents is needed in strengthening the mental and personality of adolescents.It will cause the children are not easily persuaded and fall into drug abuse. Theculture of communication based on religious values created for preventing drug useamong Muslim families so that the family can develop positive environment orvalues for their children, for creating effective communication, being a role modelfor children and supporting the healthy and positive children's activities. Theresearchers would like to thank the two families who were willing to be participantsin this study and provide the data for this research.